2020
DOI: 10.1088/1361-6528/ab5bc8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding cellular interactions with nanomaterials: towards a rational design of medical nanodevices

Abstract: Biomedical applications increasingly require fully characterized new nanomaterials. There is strong evidence showing that nanomaterials not only interact with cells passively but also actively, mediating essential molecular processes for the regulation of cellular functions, but we are only starting to understand the mechanisms of those interactions. Systematic studies about cell behavior as a response to specific nanoparticle properties are scarce in the literature even when they are necessary for the rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 130 publications
2
79
0
1
Order By: Relevance
“…Many researchers have reported that liposomes are taken up into cells via clathrin-mediated endocytosis [43,44]. In addition, it has been also suggested that around 100 nm-sized nanoparticles mainly are internalized via clathrin-mediated endocytosis [45]. Thus, we speculate that spherical CN with diameters around 120 nm is preferably suspected to internalize through a clathrin-dependent pathway.…”
Section: Discussionmentioning
confidence: 69%
“…Many researchers have reported that liposomes are taken up into cells via clathrin-mediated endocytosis [43,44]. In addition, it has been also suggested that around 100 nm-sized nanoparticles mainly are internalized via clathrin-mediated endocytosis [45]. Thus, we speculate that spherical CN with diameters around 120 nm is preferably suspected to internalize through a clathrin-dependent pathway.…”
Section: Discussionmentioning
confidence: 69%
“…Pinocytosis engulfs particle size equivalent to 100 nm whereas phagocytosis engulfs particle size larger than 0.5µm. Nanoparticles upto 50 nm penetrate via caveolin-mediated endocytosis whereas 50-100nm size nanoparticles penetrate via clathrin-mediated endocytosis (Villanueva-Flores et al, 2020). In this study, the size of synthesized CNPs ranged between 10-50 nm, the internalization mechanism shall be attributed to caveolinmediated endocytosis.…”
Section: Resultsmentioning
confidence: 71%
“…Several inconsistent reports were published on the toxicity of nanoparticles on human cells. For example, Villanueva-Flores et al (2020) suggested that nanoparticles of size less than 1.5 nm can interact with proteins or interfere with cellular channels and react causing inflammatory response or oxidative stress. On the contrary, Kokorina et al (2017) reviewed the biomedical application of non-cytotoxic carbon nanoparticles synthesized from different sources with variable size range between 0.5 and 120 nm.…”
mentioning
confidence: 99%
“…With the advent of nanotechnology, it has been possible to comprehend the cellular mechanisms of the living cells and to develop relevant technologies which facilitate early diagnosis and treatment of various viral infections [ 38 , 39 ]. Some of its applications consist of drug and gene delivery; use of fluorescent biological labels, detection of proteins, pathogens, and tumors; separation and purification of biological molecules and cells; tissue engineering; MRI contrast heightening; and pharmacokinetic studies [ 40 – 42 ].…”
Section: Introductionmentioning
confidence: 99%